Immobilization of Endo-Β-1,4-D-Xylanase using Alginate/Nanocellulose for Xylooligosaccharide Production - Ratnadewi, Anak Agung Istri; Aprilia, Selvina Rizky; Piluharto, Bambang; Yulvia, Ana (Indonesian Chimica Letters, 2023)
Free endo-β-1,4-D-xylanase cannot be used more than once, so it needs to be modified by immobilizing the enzyme. Endo-β-1,4-D-xylanase was obtained from termite abdomen sources by isolation, ammonium sulfate purification, and dialysis methods. Endo-β-1,4-D-xylanase was immobilized with an alginate/nanocellulose matrix. This study aims to determine the activity, protein content, and repeated use of immobilized Endo-β-1,4-D-xylanase. This study used variations of Alginate/nanocellulose (0; 2.5; 5; 7.5; 10) %. Protein levels of Endo-β-1,4-D-xylanase were tested using the Bradford method and activity using the Miller method. The total protein bound to the immobilized Endo-β-1,4-D-xylanase was stated with the immobilized yield data. The immobilized yield with the composition of Alginate Nanocellulose (ANC) (0%) was 45.33% greater than the other compositions. Immobilized Endo-β-1,4-D-xylanase activity is efficient. ANC 5% produces an efficiency of 62.384% at the 12th hour, which is greater than the other ANC compositions.